Quorum Sensing Regulates Exopolysaccharide Production, Motility, and Virulence in Pseudomonas syringae - Quiñones, Beatriz; Dulla, Glenn; Lindow, Steven E. (Molecular plant-microbe interactions, 2005)
The N-acyl homoserine lactone (AHL)-mediated quorumsensing system in the phytopathogen Pseudomonas syringae pv. syringae requires the AHL synthase AhlI and the regulator AhlR, and is additionally subject to regulation by AefR. The contribution of quorum sensing to the expression of a variety of traits expected to be involved in epiphytic fitness and virulence of P. syringae were examined. Both an aefR - mutant and an ahlR - double mutant, deficient in AHL production, were significantly impaired in alginate production and had an increased susceptibility to hydrogen peroxide compared with the wild-type strain. These mutants were hypermotile in culture, invaded leaves more rapidly, and caused an increased incidence of brown spot lesions on bean leaves after a 48-h moist incubation. Interestingly, an aefR - mutant was both the most motile and virulent. Like the wild-type strain, the AHL-deficient mutant strains incited water-soaked lesions on bean pods. However, lesions caused by an ahlI - ahlR - double mutant were larger, whereas those incited by an aefR - mutant were smaller. In contrast, tissue maceration of pods, which occurs at a later stage of infection, was completely abolished in the AHL-deficient mutants. Both the incidence of disease and in planta growth of P. syringae pv. tabaci were greatly reduced in transgenic tobacco plants that produced AHL compared with wild-type plants. These results demonstrate that quorum sensing in P. syringae regulates traits that contribute to epiphytic fitness as well as to distinct stages of disease development during plant infection.